The patterns of language choice at the border of Malaysia-Thailand - Jaafar, Mohammad Fadzeli; Awal, Norsimah Mat; Mis, Mohammed Azlan; Lateh, Norhayati (Universitas Pendidikan Indonesia, 2016)
Any activities conducted at the boundary area between countries will only be successful if the community of speakers has mutual understanding in terms of language, especially those involving business. This study focuses on a community in the northern part of Malaysia near the Thailand border where majority of people are bilingual in Malay and Thai. This study aims to investigate the patterns of language used by speakers in the Malaysia-Thailand border, in the context of language maintenance and language shift. Both countries use different languages; with Malaysians use Malay and the Thais use Thai language. In this cross-border context, activities pertaining to business, visit or personal matters will have an impact on the development of the two languages. This study presents the findings on the language choice from a survey involving 202 respondents that was conducted in two border towns at the Malaysia-Thailand border, namely Rantau Panjang (Malaysian side) and Golok (Thailand side). By utilizing the domain concept that was introduced by Fishman (1972), this study focuses on two domains namely, business and family. In addition to the questionnaire, participant observations and interviews were also conducted as supplements. The data on the patterns of language choice were analyzed statistically. The findings show that although Malaysians and Thais speak two different languages, Kelantanese dialect, which is a variety of the standard Malay, was the most dominant language at the border. This study also found that age was a significant factor in determining the patterns of language use. The younger generations were using Kelantanese dialect and Thai language in domains where older people would only use Kelantanese dialect. This points to the occurrence of language shift at the border. However, the community at the Thai side of the border tends to choose Kelantanese dialect in their daily activities, which seems to indicate language maintenance in this area. These findings suggest that language can serve as a marker of identity, especially for those communities in Golok as most of them are originally from Malaysia. Finally, this study has contributed empirical data on language usage at the Malaysia-Thailand border.